Adapting to the Ethics of Differentiated Learning Assessment: Analysis of Foreign-trained Teachers' Experiences in Quebec - Serigne Ben Moustapha Diédhiou; Dan Thanh Duong Thi; Arianne Robichaud (ADMEE-Canada, 2022)
In the last decade, due to the lack of teachers in Quebec, the province has welcomed a significant number of foreign-trained teachers (MEES, 2018). Research on their learning assessment skills shows that, for those teachers who get used to the standards and values of the culture of assessment for sanction in their native countries, taking into account the professionnal conventions in their host environment is a major issue to their socio-professional integration (Morrissette & Demazière, 2018a). Drawing on the theoretical approach of the social justice of Rawls (1971), we conducted a collaborative research with a group of six teachers trained in foreign countries from "meritocratic" backgrounds, to shed light on their adaptation to the ethics of differentiated assessment. The analyzes suggest a consentement that developped under the rhythm of negotiated identity conversion process through a socialization of resourcefulness in four phases: negation, discovery, learning, involvement.